Implementation of an Alternative Pathway for Patients Seeking Care for Low Back Pain: A Prospective Observational Cohort Study. Issue 12 (25th September 2018) - Magel, John; Hansen, Pamela; Meier, Whitney; Cohee, Kim; Thackeray, Anne; Hiush, Matthew; Fritz, Julie M
Abstract: Background: In the United States, low back pain (LBP) is among the most common symptoms prompting a health care visit. Patients can receive escalated care, such as advanced imaging or invasive procedures, before guideline-recommended options offered by physical therapists. A guideline-concordant alternative care pathway (RapidAccess) that emphasized early physical therapy for patients with LBP before they consulted a physiatrist was implemented. Evaluating the implementation of care pathways, such as RapidAccess using the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework, provides a broader understanding of the barriers to implementation. Objective: The purpose of this study was to evaluate the implementation of a guideline-concordant care pathway for patients with LBP using a RE-AIM framework. Design: This study used a prospective observational cohort design. Methods: Patients with a chief complaint of LBP who were scheduling a new appointment with physiatry were eligible. Eligible patients chose whether or not to participate in RapidAccess before a consultation with a physiatrist. Implementation outcomes were evaluated using the RE-AIM framework. Results: During the study period, 1556 patients with LBP called to schedule a new visit with a physiatrist. Of these, 400 (25.7%) were eligible for RapidAccess, and 124 (31% of those eligible) participated in the program (reach). Of the 400 eligible patients, 225 (56.3%) were offered RapidAccess (adoption). Compared with patients who were managed in physical therapy following a consultation with a physiatrist, RapidAccess participants demonstrated improvement in physical function with physical therapist management (effectiveness); 58.9% cancelled their physiatrist visit (implementation), and rates of imaging and injections were lower (effectiveness). Reach and adoption (maintenance) trended downward beyond the first 6 months of the project. Limitations: The results are from a single health system and might not be broadly generalizable. Conclusions: The RE-AIM framework was useful in evaluating the implementation of RapidAccess. Factors influencing reach and adoption must be further examined.